Dual functional small molecule fluorescent probes for image-guided estrogen receptor-specific targeting coupled potent antiproliferative potency for breast cancer therapy. Issue 13 (1st July 2017) - Yang, Lu; Hu, Zhiye; Luo, Junjie; Tang, Chu; Zhang, Silong; Ning, Wentao; Dong, Chune; Huang, Jian; Liu, Xianjun; Zhou, Hai-Bing
Graphical abstract: Abstract: A strategy by integrating biological imaging into early stages of the drug discovery process can improve our understanding of drug activity during preclinical and clinical study. In this article, we designed and synthesized coumarin-based nonsteroidal type fluorescence ligands for drug-target binding imaging. Among these synthesized compounds, 3e, 3f and3h showed potent ER binding affinity and3e (IC50  = 0.012 μM) exhibited excellent ER α antagonistic activity, its antiproliferative potency in breast cancer MCF-7 cells is equipotent to the approved drug tamoxifen. The fluorescence of compounds3e and3f depended on the solvent properties and showed significant changes when mixed with ER α or ER β in vitro . Furthermore, target molecule3e could cross the cell membrane, localize and image drug-target interaction in real time without cell washing. Thus, the coumarin-based platform represents a promising new ER-targeted delivery vehicle with potential imaging and therapeutic properties.